The Effect of Trust, Ease of Use, and Electronic Word of Mouth on Purchase Intention of Skintific Products Through Tiktok Shop Among Generation Z In Jakarta - Valentino AR, Michaeel; Lego , Yenny (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the influence of trust, ease of use, and electronic word of mouth on purchase intention of Skintific brand facial care products through the TikTok Store platform among Generation Z in Jakarta. Along with the increasing use of social media as a shopping platform, TikTok has become not only a means of entertainment but also an effective marketing channel for various beauty brands. Skintific as one of the popular skincare brands among young people, utilizes TikTok Store and user reviews to build trust and increase ease in the purchasing process. Generation Z as active TikTok users and potential consumers of skincare products are the main focus of this study, considering their characteristics which are highly influenced by digital reviews and ease of technology. Through a quantitative approach, this study will measure the extent to which each variable of trust, ease of use, and electronic word of mouth contributes significantly to purchase intention. The results of this study are expected to provide insight for business actors and marketers in designing more effective digital strategies to attract young consumers' buying interest, especially on rapidly growing social media platforms such as TikTok.